Long‐term variability of dust optical depths on Mars during MY24–MY32 and their impact on subtropical lower ionosphere: Climatology, modeling, and observations. Issue 8 (22nd August 2016) - Sheel, Varun; Haider, S. A.
Abstract: Dust optical depths ( τ ) for nine Martian years (MY24–MY32) in the subtropical region (25–35°S) have been used to classify distinct dust scenarios. These data are based on observations at 9.3 µm from the Mars Global Surveyor and Mars Odyssey missions and encompass the regional dust storms which occur every year around solar longitude (Ls) ~ 220° and the two major dust storms of MY25 and MY28. Constrained by these observations and the Mars Climate Sounder observations of detached dust layers, we estimate altitude profiles of dust concentrations. We discuss the characteristics of dust aerosol particles of different size between 0.2 and 3.0 µm by assuming a modified gamma distribution. We then use a comprehensive ion‐dust model to calculate ion densities and conductivities in the lower ionosphere of Mars in the absence of dust storm at τ  = 0.1 and Ls = 150° and for three dust storm periods viz., (1) major dust storm at τ  = 1.7 and Ls = 210°, (2) major dust storm at τ  = 1.2 and Ls = 280°, and (3) regional dust storm at τ  = 0.5 and Ls = 220°. The model with 12 neutral species considers galactic cosmic rays as a source of ionization. Results show that the density of the dominant hydrated cluster ions and the electrical conductivity are reduced by an order of magnitude near the surface for a few months until the dust storm settles down to its normal condition. Key Points: A climatology of dust (MY24–MY32) in southern subtropics helps classify distinct dust scenarios An ion‐dust model is used to evaluate the effect of these dust conditions on lower ionosophere Results show that ion density and conductivity near the surface are reduced by an order of magnitude during dust storms